Interactive controls of herbivory and fluvial dynamics on landscape vegetation patterns on the Tanana River floodplain, interior Alaska - Lem G. Butler; Knut Kielland; T. Scott Rupp; Thomas A. Hanley (Journal of Biogeography, 2007)
Aim We examined the interactive effects of mammalian herbivory and fluvial dynamics on vegetation dynamics and composition along the Tanana River in interior Alaska. Location Model parameters were obtained from field studies along the Tanana River, Alaska between Fairbanks (64°50.50′ N, 147°43.30′ W) and Manley Hot Springs (65°0.0′ N, 150°36.0′ W). Methods We used a spatially explicit model of landscape dynamics (ALFRESCO) to simulate vegetation changes on a 1‐year time‐step. The model was run for 250 years and was replicated 100 times. Results Increases in herbivory decreased the proportion of early successional vegetation and increased the proportion of late successional vegetation on the simulated landscape. Erosion and accretion worked as antagonists to herbivory, increasing the amount of early successional vegetation and decreasing the amount of late successional vegetation. However, the interactive effects of herbivory and erosion/accretion were especially important in determining system response, particularly in early seral vegetation types. High erosion rates, when coupled with low herbivory, greatly increased the proportion of willow on the landscape. When coupled with high herbivory, however, they greatly increased the proportion of alder on the landscape. At low levels of herbivory, alder abundance peaked at intermediate levels of erosion/accretion. Main conclusions Neither erosion/accretion nor herbivory produced consistent landscape patterns that could be predicted independently of the other. These findings underscore the importance of the interactive effects of biotic and abiotic disturbances in shaping large‐scale landscape vegetation patterns in boreal floodplain ecosystems – systems traditionally thought to be driven primarily by abiotic disturbance alone.